2017
DOI: 10.1007/s40620-017-0419-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety in ESA biosimilars vs. originators in adults with chronic kidney disease: a systematic review and meta-analysis

Abstract: Data from 31 included studies allowed to pool data in meta-analysis related to four different comparisons and eleven outcome measures. Nevertheless, only one result was statistically significant in favor of darbepoetin α in the comparison with epoetin α concerning blood transfusions. For all the other outcomes and comparisons, we did not find any differences in terms of efficacy and security between the EPO considered. The quality of evidence is quite low, and further research could change these results. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The type of ESA may play a role in the risk of adverse outcomes, but the relative risk among individual ESAs remains controversial. In a large, long-term, randomized trial, patients with CKD receiving epoetin beta pegol had no increase in risk of all-cause mortality, nonfatal myocardial infarction, or stroke compared to those receiving either epoetin alfa or darbepoetin alfa [36], in agreement with prior meta-analyses that found no significant safety differences among ESAs [37][38][39]. A recent pooled analysis of prospective cohorts in Italy with non-dialysis-dependent (NDD) CKD stages 1-5 showed that the risk of the composite of end-stage kidney disease or death was not impacted by the type of ESA (e.g., short-acting [epoetin alfa or epoetin beta] or long-acting [darbepoetin alfa or epoetin beta pegol]) when all dosing levels were pooled but did increase at higher standardized ESA doses [40].…”
Section: Prevalence and Characteristics Of Esa Hyporesponsesupporting
confidence: 82%
“…The type of ESA may play a role in the risk of adverse outcomes, but the relative risk among individual ESAs remains controversial. In a large, long-term, randomized trial, patients with CKD receiving epoetin beta pegol had no increase in risk of all-cause mortality, nonfatal myocardial infarction, or stroke compared to those receiving either epoetin alfa or darbepoetin alfa [36], in agreement with prior meta-analyses that found no significant safety differences among ESAs [37][38][39]. A recent pooled analysis of prospective cohorts in Italy with non-dialysis-dependent (NDD) CKD stages 1-5 showed that the risk of the composite of end-stage kidney disease or death was not impacted by the type of ESA (e.g., short-acting [epoetin alfa or epoetin beta] or long-acting [darbepoetin alfa or epoetin beta pegol]) when all dosing levels were pooled but did increase at higher standardized ESA doses [40].…”
Section: Prevalence and Characteristics Of Esa Hyporesponsesupporting
confidence: 82%
“…For biosimilars, both of the included meta-analyses 27,28 and one 29 of the two RCTs 29,30 involved patients with CKD. The only RCT in patients with cancer 30 had a high likelihood of bias based on inadequate sample size, lack of an intent-to-treat analysis, and industry funding and authorship.…”
Section: Resultsmentioning
confidence: 99%
“…The systematic review of biosimilar ESAs included two metaanalyses 27,28 and one RCT 29 in patients with CKD, and one RCT 30 and three cohort studies [31][32][33] in patients with cancer. In a 2017 meta-analysis of RCTs in CKD, Amato et al 27 reported that efficacy and safety outcomes did not differ significantly between patients treated with epoetin alfa originator or biosimilar but described the quality of evidence as low to very low. A 2017 Cochrane review by Hahn et al 28 focused on short-acting ESAs in predialysis patients.…”
Section: Recommendationmentioning
confidence: 99%
“…Several reviews also contributed to ascertaining the available evidence on the consequences of switching from originators to related biosimilars, although they were not focused exclusively on ESAs [20, 22, 32]. In particular, these three studies did not find any differences in terms of immunogenicity, safety or efficacy between those continuing therapy with originators or those switching to biosimilars, thus indicating that concerns related to switching have been so far unsupported.…”
Section: Discussionmentioning
confidence: 99%